Complications After Laparoscopic Sleeve Gastrectomy in a Series of 186 Patients - Toni Stoyanov; Pedro Cascales-Sánchez; Agustina Moreno (Journal of Biomedical & Clinical Research)
A retrospective study analyzed the complications in 186 patients who underwent laparoscopic sleeve gastrectomy (LSG). One hundred eighty-four patients were operated on at the University Hospital Centre of Albacete between May 2006 and September 2022. Two patients with early postoperative complications received surgical treatment in other centers. The overall postoperative complication rate (including GERD) was 13.9%. Ten patients (5.38%) had complications in the early postoperative period. In 4 cases (2.15%), there was stapler-line leakage. Abdominal bleeding associated with hemoperitoneum occurred in four patients (2.15%) immediately after the surgery due to bleeding from the suture line. In the long-term follow-up, two patients (1.08%) had gastric tube strictures requiring endoscopic pneumatic balloon dilation (EPBD). Fourteen patients (7.53%) presented with de novo Gastroesophageal Reflux, of whom 7 (3.76%) required revision surgery to Laparoscopic Rouxen-Y Gastric Bypass (LRYGB). Laparoscopic sleeve gastrectomy, in our experience, is a secure bariatric procedure with a low rate of morbidity and mortality, both post-surgical and long-term.